Analisis Penerapan Pencatatan Akuntansi Melalui Pendekatan Accrual Basic Ditinjau Dari Perspektif Akuntansi Syariah (Studi Kasus Pada Toko Tura Tas Pasar Sentral Palakka Kab. Bone) - Alviana; Ahmad Abdul Mutalib; Fitriani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the implementation of accrual basic accounting records at the Tura Tas Store in Palakka Central Market, Bone Regency, and to review its compliance with sharia accounting principles. Good financial records not only provide a clear picture of financial conditions, but also function as a strategic decision-making tool in running a business. This study uses a qualitative method with a field approach, involving interviews and observations of the owner and employees of the Tura Tas Store. The results of the study indicate that the Tura Tas Store has not fully implemented accrual basic records because the financial records carried out only include income, expenses, and receivables. However, these records are still done manually. In accrual basic accounting, recording receivables is an important thing that reflects that income has been obtained even though cash has not been received, and is recognized as an asset. In addition, the Tura Tas Store has not fully implemented sharia accounting principles.